Substrate laminate and method for manufacturing said substrate laminate

JP7634403B2Active Publication Date: 2025-02-21KANEKA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021054898
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-02-21
Estimated Expiration
2041-03-29

AI Technical Summary

Benefits of technology

【0021】 本発明の基板積層体を用いることで、高温高湿保存試験時にガラスヤケが抑制された信頼性に優れた基板積層体が得られるという効果を奏する。また、本発明の基板積層体を用いれば、高温多湿な状況下でも使用可能な中空構造体を提供することができ、特にCMOS·CCDセンサ用中空構造体、MEMSデバイス用中空構造体の製造に適している。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634403000004
    Figure 0007634403000004
  • Figure 0007634403000005
    Figure 0007634403000005
  • Figure 0007634403000006
    Figure 0007634403000006
Patent Text Reader

Abstract

To provide a substrate laminate and a method for manufacturing the same, in which the occurrence of glass burning under high temperature and high humidity conditions is suppressed.SOLUTION: A substrate laminate having a glass substrate 2 as the first substrate, an adhesive layer 1, and a semiconductor device substrate 3 as the second substrate, has a hollow space between the first and second substrates and an adhesive layer on the periphery of the hollow space, and either the first or second substrate is glass containing an alkali component and a layer containing an organic acid compound on the hollow side surface of the glass containing an alkali component.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a substrate stack and a method for manufacturing a substrate stack. [Background technology]

[0002] In MEMS sensors such as image sensors, acceleration sensors, and pressure sensors, in order to ensure light transparency and the movement of mechanical parts, it is necessary to provide a hollow space in the semiconductor package and bond a sealing substrate made of glass, metal, ceramic, etc., with an adhesive placed around the periphery of the package. Conventionally, a bonding method using a curable resin such as a thermosetting resin or a photosensitive resin as the adhesive has been used (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-041410 A Summary of the Invention [Problem to be solved by the invention]

[0004] When non-alkali glass is used as a sealing substrate, the linear expansion coefficient of the non-alkali glass is different from that of the curable resin used as an adhesive, so cracks may occur in the curable resin during reflow at high temperatures, which may reduce the reliability of the semiconductor element. In addition, non-alkali glass is susceptible to alpha rays, which may deteriorate the imaging characteristics of the image sensor. On the other hand, glass containing alkaline components has a linear expansion coefficient close to that of the curable resin, so it is less likely to crack and can suppress the incidence of alpha rays. However, it has been found that during high-temperature and high-humidity storage tests, "glass discoloration" occurs on the glass in the hollow part, due to the elution of alkaline components such as sodium and potassium in the glass, which may deteriorate the imaging characteristics of the image sensor.

[0005] The present invention has been made in consideration of the above-mentioned points, and has an object to provide a substrate laminate having two substrates and an adhesive layer, at least one of which is glass containing an alkaline component, in which glass tarnishing is suppressed in a high-temperature, high-humidity storage test, and a method for manufacturing the substrate laminate. [Means for solving the problem]

[0006] As a result of earnest research by the inventors to solve the above problems, the present invention has been completed by discovering that the above problems can be solved by a substrate laminate having a first substrate, an adhesive layer, and a second substrate, a hollow portion between the first substrate and the second substrate, the adhesive layer being disposed on the outer periphery of the hollow portion, one of the first substrate and the second substrate being made of glass containing an alkaline component, and a layer containing an organic acidic compound being disposed on the surface of the glass containing an alkaline component facing the hollow portion. That is, the present invention has the following configuration.

[0007] [1]. A substrate laminate having a first substrate, an adhesive layer, and a second substrate, the substrate laminate having a hollow portion between the first substrate and the second substrate, the adhesive layer being disposed on the outer periphery of the hollow portion, one of the first substrate and the second substrate being made of glass containing an alkaline component, and the substrate laminate having a layer containing an organic acidic compound on the surface of the glass containing an alkaline component facing the hollow portion.

[0008] [2] The substrate laminate according to [1], wherein the boiling point of the organic acidic compound is 300°C or lower.

[0009] [3] The substrate laminate according to [1] or [2], wherein the organic acidic compound has a molecular weight of 300 or less.

[0010] [4] The substrate laminate according to any one of [1] to [3], wherein the organic acidic compound has an acid dissociation constant (pKa) of 2.5 to 10.

[0011] [5] The substrate laminate according to any one of [1] to [4], wherein the organic acidic compound has at least one functional group selected from the group consisting of a carboxyl group, a phosphorus (P)-containing acidic group, a phosphorus (P)-containing ester group, a sulfo group, a sulfonyl group, an amide group, and a cyanuric group.

[0012] [6] The substrate laminate according to any one of [1] to [5], wherein the adhesive layer contains at least one resin selected from the group consisting of an epoxy resin, an acrylic resin, a polyimide resin, a phenolic resin, and a silicone resin.

[0013] [7] The substrate laminate according to any one of [1] to [6], wherein the adhesive layer has cationic polymerization properties.

[0014] [8] The substrate laminate according to any one of [1] to [7], wherein the adhesive layer is a photosensitive resin.

[0015] [9] The substrate laminate according to any one of [1] to [8], wherein the adhesive layer is alkali-soluble.

[0016]

[10] The substrate laminate according to any one of [1] to [9], wherein the other of the first substrate and the second substrate is a semiconductor device substrate.

[0017]

[11] A method for producing a substrate laminate, comprising: forming an adhesive layer containing a curable resin and at least one organic acidic compound in a pattern on a first substrate; laminating a surface of the first substrate on the adhesive layer side with a second substrate to obtain a laminate; and heating the laminate at 180°C to 350°C, wherein either the first substrate or the second substrate is glass containing an alkali component.

[0018]

[12] The method for producing a substrate laminate according to

[11] , wherein the organic acidic compound is 0.1 to 15 parts by weight relative to 100 parts by weight of the curable resin.

[0019]

[13] The method for manufacturing a substrate laminate according to

[11] or

[12] , which has a hollow portion surrounded by the first substrate, the second substrate, and the adhesive layer.

[0020]

[14] The method for producing a substrate laminate according to any one of

[11] to

[13] , wherein the other of the first substrate and the second substrate is a semiconductor element substrate. Effect of the Invention

[0021] The use of the substrate laminate of the present invention has the effect of providing a substrate laminate with excellent reliability in which glass tarnish is suppressed during a high-temperature, high-humidity storage test. In addition, the use of the substrate laminate of the present invention makes it possible to provide a hollow structure that can be used even under high-temperature, high-humidity conditions, and is particularly suitable for manufacturing hollow structures for CMOS / CCD sensors and hollow structures for MEMS devices. [Brief description of the drawings]

[0022] [Figure 1] 1A to 1C are explanatory diagrams showing a method for manufacturing a substrate laminate according to one embodiment of the present invention. [Diagram 2] 10A to 10C are explanatory diagrams showing a method for manufacturing a substrate laminate according to another embodiment of the present invention. [Diagram 3] 10A to 10C are explanatory diagrams showing a method for manufacturing a substrate laminate according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The embodiments of the present invention will be described in detail below. Unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and larger than A) and B or less (including B and smaller than B)."

[0024] 1. Substrate Laminate The substrate laminate in the present invention is a substrate laminate having a first substrate, an adhesive layer, and a second substrate, having a hollow portion between the first substrate and the second substrate, having the adhesive layer on the outer periphery of the hollow portion, either the first substrate or the second substrate being glass containing an alkali component, and having a layer containing an organic acidic compound on the surface of the glass containing an alkali component facing the hollow portion.

[0025] Either the first substrate or the second substrate is a glass containing an alkali component, and specific examples include BDA, BDA-E, G-Leaf, glass ribbon, Dinorex (borosilicate glass, manufactured by Nippon Electric Glass Co., Ltd.), D263 series, MEMpax, TEMPAX Float (borosilicate glass, manufactured by Schott), etc. Among these, from the viewpoint of correctly transmitting optical signals, BDA, BDA-E, and D263 are preferred, which are characterized by a smooth surface and easy dicing and cutting.

[0026] The glass containing an alkaline component used as the first substrate or the second substrate has a layer containing an organic acidic compound on the surface facing the hollow portion. By having the layer containing an organic acidic compound, even if moisture penetrates into the hollow portion of the substrate laminate in a high-temperature and high-humidity environment, glass tarnish caused by the elution of alkaline components such as sodium and potassium contained in the glass containing an alkaline component can be suppressed.

[0027] The layer containing an organic acidic compound may be formed by coating the surface of glass containing an alkaline component before the production of the substrate laminate, or may be formed by using a curable resin containing an organic acidic compound as an adhesive layer and generating and attaching the organic acidic compound as an outgas during the production of the substrate laminate. Details of the organic acidic compound will be described later.

[0028] Substrates that can be used as the other substrate in the substrate laminate of the present invention include a semiconductor element substrate (sensor substrate), a silicon wafer, a transparent substrate (e.g., an alkali-free glass substrate, a transparent resin substrate), a colored resin substrate, and a ceramic substrate. In the manufacture of an image sensor described later, a sensor substrate is used as the first substrate and a glass substrate containing an alkali component is used as the second substrate, or a glass substrate containing an alkali component is used as the first substrate and a sensor substrate is used as the second substrate. The shape of the substrate may be round or square. Since existing semiconductor manufacturing equipment can be used, it is preferable to use a round substrate of 4 inches to 12 inches. The sizes of the first substrate and the second substrate may be the same or different.

[0029] The substrate laminate of the present invention can easily obtain a hollow structure by appropriately selecting the width and height of the adhesive layer. In particular, when the substrate laminate is used as a structure for a CMOS / CCD sensor, if the adhesive layer is too low, the sensor substrate may be damaged during assembly, or ghosts and flares may occur, causing deterioration of imaging characteristics. If the adhesive layer is too high, a stable cross-sectional shape may not be obtained, and the adhesive performance may deteriorate. From these points, the height of the adhesive layer is 1 μm to 200 μm, preferably 50 μm to 150 μm. If the width of the adhesive layer is too thin, sufficient adhesive strength cannot be obtained. If the width of the adhesive layer is too wide, there will be no space to place the sensor substrate. From these points, the width of the adhesive layer is 1 μm to 1000 μm, preferably 100 μm to 250 μm.

[0030] The substrate laminate of the present invention has a hollow portion between the first substrate and the second substrate, and has an adhesive layer on the outer periphery of the hollow portion. In other words, the hollow portion is formed by the first substrate, the second substrate, and the adhesive layer. The adhesive layer is not particularly limited as long as it can form a hollow portion when viewed from a direction perpendicular to the first substrate or the second substrate, but is preferably formed in a pattern shape from the viewpoint of adhesion reliability and productivity. Examples of the pattern shape include a square shape, a hexagonal shape, and a circle shape.

[0031] [2. Organic acidic compounds] A layer containing an organic acidic compound is formed on the hollow part side of the glass containing an alkaline component. Glass tarnish of glass containing an alkaline component is generally caused by the alkaline component in the glass dissolving in the moisture attached to the glass surface and reacting (chlorinating) with carbon dioxide or the like in the air. On the other hand, if a layer of an organic acidic compound is present on the surface of the glass containing an alkaline component, the organic acidic compound dissolves in the water attached to the glass surface, thereby suppressing the dissolution of the alkaline component in the glass. Therefore, the organic acidic compound to be used is not particularly limited as long as it shows the above-mentioned reactivity, but from the viewpoint of hydrophilicity, an acidic compound having at least one functional group selected from the group consisting of a carboxyl group, an acidic group containing phosphorus (P), an ester group containing phosphorus (P), a sulfo group, a sulfonyl group, an amide group, and a cyanuric group is preferable. In particular, from the viewpoint of hydrophilicity and the acidity described later, a carboxyl group, an acidic group containing phosphorus (P), and an ester group containing phosphorus (P) are preferable.

[0032] In addition, when the curable resin contains an organic acidic compound as an additive, it is necessary to volatilize the organic acidic compound as an outgas in the heating process into the hollow of the substrate laminate in order to form a layer of the organic acidic compound on the glass surface. For example, when the substrate laminate obtained by the present invention is used for an image sensor or MEMS sensor, it is more effective to use an organic acidic compound with a boiling point lower than the highest reflow temperature of 260°C or close to the reflow temperature. Therefore, the upper limit of the boiling point of the organic acidic compound is preferably 300°C or less, more preferably 200°C or less. As for the lower limit of the boiling point, since a layer can be efficiently formed on the glass surface having an alkaline component, it is preferably 23°C or more, more preferably 60°C or more.

[0033] From the same viewpoint as for the boiling point described above, the upper limit of the molecular weight of the organic acidic compound is preferably 300 or less, more preferably 200 or less. From the same viewpoint as for the boiling point described above, the lower limit of the molecular weight is preferably 40 or more, more preferably 60 or more.

[0034] Furthermore, when an organic acidic compound is contained as an additive in a curable resin, if the acidity is too high, problems such as deterioration of the storage stability of the curable resin and an increase in the amount of outgassing due to cleavage of the formed bonds occur. Therefore, the acid dissociation constant (pKa) of the organic acidic compound when added to a curable resin is preferably 2.5 to 10, more preferably 2.5 to 7, and particularly preferably 3 to 5.

[0035] Examples of organic acidic compounds having a carboxyl group include linear or branched saturated carboxylic acids having 1 to 10 carbon atoms, such as formic acid, acetic acid, propionic acid, butanoic acid, hexanoic acid, and octylic acid; unsaturated carboxylic acids, such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, benzoic acid, and sorbic acid; dibasic acids, such as oxalic acid, malonic acid, sebacic acid, maleic acid, fumaric acid, and itaconic acid; and aromatic carboxylic acids, such as benzoic acid. Among these, acetic acid, propionic acid, malonic acid, and benzoic acid are preferred because of their excellent balance between acidity and hydrophilicity.

[0036] Examples of organic acidic compounds having an acidic group containing phosphorus (P) or an ester group containing phosphorus (P) include ethylphosphinic acid, dimethylphosphinic acid, butylphosphinic acid, butoxyethylphosphinic acid, octylphosphinic acid, (3-hydroxypropyl)butylphosphinic acid, (3-hydroxypropyl)octylphosphinic acid, dibutylphosphinic acid, dioctylphosphinic acid, 3-hydroxypropylphosphinic acid, 2-hydroxyethylmethacrylatephosphinic acid, phenylphosphinic acid, diphenylphosphinic acid, etc. In particular, ethylphosphinic acid, dimethylphosphinic acid, butylphosphinic acid, and (3-hydroxypropyl)octylphosphinic acid are preferred because of their excellent balance between acidity and hydrophilicity.

[0037] Examples of organic acidic compounds having a sulfo group or a sulfonyl group include methanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, 10-camphorsulfonic acid, trifluorosulfonic acid, aminoethanesulfonic acid, aminopropanesulfonic acid, and ester derivatives thereof, etc. In particular, ester derivatives of methanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid are preferred because they have an excellent balance between boiling point and acidity.

[0038] Examples of organic acidic compounds having an amide group include acetamide, acrylamide, malonamide, succinamide, maleamide, fumaramide, benzamide, 2-naphthamide, phthalamide, isonylamide, terephthalamide, nicotinamide, isonicotinamide, 2-furamide, formamide, propionamide, propiolamide, butylamide, isobutylamide, methacrylamide, oxamide, glycolamide, lactamide, glyceramide, pyruvamide, acetoacetamide, benzylamide, diacetamide, triacetamide, dibenzamide, tribenzamide, etc. Malonamide, maleamide, fumaramide, terephthalamide, nicotinamide, and isonicotinamide are particularly preferred because of their excellent balance between boiling point and acidity.

[0039] Examples of organic acidic compounds having a cyanuric group include bromoiso-2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, naphthalene-1,5-diisocyanate, o-xylylene diisocyanate, m-xylylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, methylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4-methylenebis(cyclohexyl isocyanate), isophorone diisocyanate, bicycloheptane triisocyanate, melanin cyanurate, cyanuric acid, etc. Bromoiso-2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, isophorone diisocyanate, and melanin cyanurate are particularly preferred because of their excellent balance between boiling point and acidity.

[0040] [3. Adhesive layer] (curable resin) In the present invention, it is preferable to use a curable resin for the adhesive layer from the viewpoint of adhesive reliability and handling. The curable resin in the present invention refers to a resin that is cured by heat, light, or heat and light. The curable resin is in an uncured or semi-cured state and is not completely cured, so it can function as an adhesive layer that constitutes a substrate laminate. In addition, the curable resin of the present invention preferably contains at least one selected from the group consisting of epoxy resin, acrylic resin, polyimide resin, phenolic resin, and silicone resin.

[0041] Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, etc. The epoxy resins may be used alone or in combination of two or more. In particular, from the viewpoint of adhesiveness, it is preferable to use one or more types selected from bisphenol A type epoxy resins, bisphenol F type epoxy resins, and biphenyl type epoxy resins.

[0042] The content of the epoxy resin in the curable resin is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 15% by weight or more, from the viewpoint of obtaining an insulating layer exhibiting good mechanical strength and insulating reliability. The upper limit of the content of the epoxy resin is not particularly limited as long as the effects of the present invention are exhibited, but is preferably 50% by weight or less. Examples of commercially available epoxy resins include jER828, jER806, jER807, YX8000, YX8034, and YX834 manufactured by Mitsubishi Chemical Corporation, YD-128, YDF-170, ZX-1059, and ST-3000 manufactured by Nippon Steel Chemical & Material Co., Ltd., EPICLON830, EPICLON835, EPICLON840, EPICLON850, N-730A, and N-695 manufactured by DIC Corporation, and RE-306 manufactured by Nippon Kayaku Co., Ltd.

[0043] The acrylic resin is preferably, for example, a carboxyl group-containing acrylic ester copolymer resin, an epoxy group-containing acrylic ester copolymer resin, a hydroxyl group-containing acrylic ester copolymer resin, or a resin containing an acrylic copolymer as the main component (preferably 80% by weight or more).Furthermore, the acrylic copolymer used is preferably an acrylic copolymer having at least an epoxy group and a carboxyl group as essential components in the side chain.

[0044] Acrylic resins are highly compatible with epoxy resins and are preferably used for viscoelasticity control. Commercially available acrylic resins include, for example, Teisan Resin SG-70L, SG-708-6, WS-023, SG-700AS, SG-280TEA, SG-80H, SG-80H-3, SG-P3, SG-600TEA, and SG-790 manufactured by Nagase Chemtex Corporation, and ME-2000, W-116.3, W-197C, KG-25, and KG-3000 manufactured by Negami Chemical Industries Co., Ltd.

[0045] Examples of polyimide resins include condensation type polyimides, bismaleimide type polyimides, nadic acid type polyimides, acetylene type polyimides, allylnadimide type polyimides, maleimide type polyimides, triazine type polyimides, and Michael addition type polyimides.

[0046] Polyimide resins have high high-temperature properties and are suitable for use in improving reflow resistance. In addition, condensation water and other volatile substances are not generated during curing, and voids and cracks are unlikely to occur. Commercially available polyimide resins include Ube Industries' Upilex-S, Upilex-SGA, Upilex-VT, Upilex-NVT, Upia-ST, Upia-AT, Toray DuPont's Falda, Photoneece, Kapton, Panacol-Elosol GmbH's Elecolit, and Somar's SPIXARIAAD.

[0047] Examples of the phenol resin include bisphenol type phenol resin, aralkyl type phenol resin, phosphorus atom-containing phenol resin, resol type phenol resin, and novolac type phenol resin.

[0048] Phenol-based resins have high electrical insulation properties and are suitable for use in electronic materials. They also have high acid resistance, and the cured resin components are less likely to decompose even when an organic acidic compound is added. Commercially available phenol-based resins include PR-30-40P, PR-100L-50P, PR-50, PR-55, WR-101, WR-102, WR-103, and WR-104 manufactured by DIC, and DL-92, HF-1M, MEHC-7800, MEHC-7851, MEHC-7841-4S, MEH-7500, MEH-7600-4H, and MEH7000 manufactured by Meiwa Kasei Co., Ltd.

[0049] The silicone resin may be a type containing the silicone resin as a main component, or may be a modified silicone type with an organic resin such as a urethane resin, an epoxy resin, or an acrylic resin, etc. Examples of the silicone resin include an addition type silicone resin, a condensation type silicone resin, an ultraviolet-curable silicone resin, an electron beam-curable silicone resin, and a solventless silicone resin.

[0050] Silicone resins have high heat resistance and excellent electrical insulation, so they are suitable for use in electronic materials.Commercially available silicone resins include, for example, KS-774, KS-775, KS-778, KS-779H, KS-856, X-62-2422, and X-62-2461 manufactured by Shin-Etsu Chemical Co., Ltd.; DKQ3-202, DKQ3-203, DKQ3-204, DKQ3-205, and DKQ3-210 manufactured by Dow Corning Asia Co., Ltd.; YSR-3022, TPR-6700, TPR-6720, and TPR-6721 manufactured by Toshiba Silicone Co., Ltd.; and SD7220, SD7226, and SD7229 manufactured by Dow Corning Toray Co., Ltd.

[0051] Among the above-mentioned resins, it is preferable to use either an epoxy resin or a silicone resin, from the viewpoint of heat resistance that does not peel off when the package expands during reflow, and adhesive strength.

[0052] (alkali soluble) The curable resin used in the adhesive layer of the present invention is preferably a photosensitive resin since it can form a delicate pattern shape. In particular, it is preferable that the curable resin has alkali solubility from the viewpoints of compatibility with conventional manufacturing equipment and reduction of environmental burden, since an alkaline aqueous solution can be used as a developer instead of an organic solvent in the pattern formation process by photolithography. As an alkali soluble group that exhibits alkali solubility, for example, the curable resin may have the following formula (X1) or (X2) as an alkali soluble group.

[0053] [ka]

[0054] In view of heat resistance and ability to reduce swelling of a pattern due to alkaline development, the structures represented by formula (X1) or (X2) are preferred.

[0055] The amount of alkali-soluble groups in the curable resin of the present invention is preferably 1 to 90 parts by weight of the curable resin, and more preferably 5 to 60 parts by weight, which is appropriate for patterning.

[0056] (cationic polymerizable) The curable resin in the present invention is preferably cationic polymerizable because it can provide sufficient adhesive strength to withstand the reflow process. Resins that exhibit cationic polymerizability include resins having cationic polymerizable functional groups such as epoxy groups, oxetane groups, and vinyl ether groups. Specifically, novolac phenol type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, cyclohexyl epoxy group-containing polyorganosiloxanes (cyclic or linear), glycidyl group-containing polyorganosiloxanes (cyclic or linear), bisphenol F diglycidyl ether, bisphenol A diglycidyl ether, 2,2'-bis(4-glycidyloxycyclohexyl)propane, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, vinylcyclohexene dioxide, 2-(3,4-epoxycyclohexyl)-5, Examples of such bisglycidyl esters include 5-spiro-(3,4-epoxycyclohexane)-1,3-dioxane, bis(3,4-epoxycyclohexyl)adipate, 1,2-cyclopropanedicarboxylic acid bisglycidyl ester, triglycidyl isocyanurate, monoallyl diglycidyl isocyanurate, diallyl monoglycidyl isocyanurate, 1,4-bis{(3-ethyl-3-oxetanyl)methoxy}methyl}benzene, bis{1-ethyl(3-oxetanyl)}methyl ether, 3-ethyl-3-(phenoxymethyl)oxetane, and 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane.

[0057] Among the cationic polymerizable functional groups, an epoxy group is preferred from the viewpoint of stability, and among the epoxy groups, an alicyclic epoxy group or a glycidyl group is preferred, and in particular, an alicyclic epoxy group is preferred from the viewpoint of excellent cationic polymerizability by light and heat. A resin exhibiting cationic polymerizability may have at least one cationic polymerizable functional group in one molecule, but it is preferable to have two or more, and more preferable to have three or more. If there are three or more cationic polymerizable functional groups, a cured product with high crosslink density can be obtained, and the cured product has the advantage of excellent heat resistance. Each cationic polymerizable functional group may be the same or may be two or more different functional groups.

[0058] The amount of the cationically polymerizable group in the curable resin of the present invention is preferably 1 to 90 parts by weight, and more preferably 5 to 60 parts by weight, of the curable resin.

[0059] The curable resin in the present invention is preferably alkali-soluble and cationic polymerizable. The curable resin used in the adhesive layer of the present invention may be a mixture of an alkali-soluble molecule and a cationic polymerizable molecule, but from the viewpoint of patterning, it is preferable that the curable resin has both alkali-solubility and cationic polymerizability in one molecule.

[0060] (Polysiloxane compounds) The curable resin used in the adhesive layer of the present invention preferably contains a polysiloxane compound from the viewpoints of heat resistance during reflow and reducing outgassing. In the present invention, the polysiloxane compound is not particularly limited as long as it is a compound having a siloxane unit Si-O-Si. Among the siloxane units in the polysiloxane compound, T units (XSiO 3 / 2 ) or Q units (SiO 4 / 2 The higher the content of XSiO, the harder the resulting cured product will be and the more heat-resistant and reliable it will be. 1 / 2 ) or D units (XSiO 2 / 2 The higher the content of ), the more flexible and low stress the resulting cured product will be.

[0061] From the viewpoints of compatibility with other components and patterning properties, the polysiloxane compound in the curable resin preferably has a cationically polymerizable group in the molecule, and more preferably has a cationically polymerizable group and an alkali-soluble group in the molecule.

[0062] [4. Other Additives] (Crosslinking agent) In order to adjust the workability, reactivity, adhesiveness and strength of the cured product, a crosslinking agent having two or more photopolymerizable functional groups other than cationic polymerizable functional groups in one molecule can be added to the curable resin. The crosslinking agent is not particularly limited as long as it is selected according to the curing reaction type, and includes alkoxysilane compounds and (meth)acrylate compounds.

[0063] (Photoacid generator) When the curable resin is a photosensitive resin, it is preferable to contain a photoacid generator. The photoacid generator is not particularly limited as long as it is a compound that can release an acidic active substance that can crosslink the photopolymerizable functional group of the curable resin by being irradiated with active energy rays.

[0064] As the photoacid generator, known photoacid generators can be used.For example, as the photoacid generator, various compounds that are considered to be suitable in JP-A-2000-1648, JP-T-2001-515533 and WO-A-2002 / 83764 can be listed, but are not limited thereto.The photoacid generator is preferably sulfonate esters, carboxylate esters or onium salts, more preferably onium salts.

[0065] As the sulfonate esters, various sulfonic acid derivatives can be used, for example, disulfones, disulfonyldiazomethanes, disulfonylmethanes, sulfonylbenzoylmethanes, imide sulfonates such as trifluoromethylsulfonate derivatives, benzoin sulfonates, sulfonates of 1-oxy-2-hydroxy-3-propyl alcohol, pyrogallol trisulfonates, and benzylsulfonates.

[0066] Specific examples of the sulfonate esters include diphenyl disulfone, ditosyl disulfone, bis(phenylsulfonyl)diazomethane, bis(chlorophenylsulfonyl)diazomethane, bis(xylylsulfonyl)diazomethane, phenylsulfonylbenzoyldiazomethane, bis(cyclohexylsulfonyl)methane, 1,8-naphthalenedicarboxylic acid imide methyl sulfonate, 1,8-naphthalenedicarboxylic acid imide tosyl sulfonate, 1,8-naphthalenedicarboxylic acid imide trifluoromethyl sulfonate, 1,8-naphthalenedicarboxylic acid imide camphorsulfonate, succinic acid imide phenyl sulfonate, succinic acid imide dotosylsulfonate, succinimide trifluoromethylsulfonate, succinimide camphorsulfonate, phthalimide trifluorosulfonate, cis-5-norbornene-endo-2,3-dicarboxylic acid imide trifluoromethylsulfonate, benzoin tosylate, 1,2-diphenyl-2-hydroxypropyl tosylate, 1,2-di(4-methylmercaptophenyl)-2-hydroxypropyl tosylate, pyrogallol methylsulfonate, pyrogallol ethylsulfonate, 2,6-dinitrophenyl methyl tosylate, ortho-nitrophenyl methyl tosylate, and para-nitrophenyl tosylate.

[0067] These may be used alone or in combination of two or more. In the present invention, carboxylic acid esters may also be used as photoacid generators.

[0068] In general, sulfonate esters and carboxylate esters may require a heating step (50° C.-100° C.) to liberate the acid.

[0069] The onium salt is tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), hexafluoroantimonate (SbF6 - ), hexafluoroarsenate (AsF6 -), hexachloroantimonate (SbCl6 - ), tetraphenylborate, tetrakis(trifluoromethylphenyl)borate, tetrakis(pentafluoromethylphenyl)borate, fluoroalkyl fluorophosphate, perchlorate ion (ClO4 - ), trifluoromethanesulfonate ion (CF3SO3 - ), fluorosulfonate ion (FSO3 - ), sulfonium salts and iodonium salts having anions such as toluenesulfonate ion, trinitrobenzenesulfonate anion, and trinitrotoluenesulfonate anion. From the viewpoint of absorption wavelength, the photoacid generator is preferably an aromatic sulfonium salt.

[0070] The anions in photoacid generators are listed in order of acid strength from strongest to weakest: SbF6 - , B(C6F5)4 - , PF6 - , CF3SO3 - , HSO4 - The stronger the acid strength of the anion of the photoacid generator, the higher the film remaining rate tends to be. The pKa of the acid generated from the photoacid generator is preferably less than 3, and more preferably less than 1.

[0071] The content of the photoacid generator is not particularly limited, but from the viewpoint of the balance between the curing speed and the physical properties of the cured product, the content of the photoacid generator is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, per 100 parts by weight of the curable resin.

[0072] If the amount of photoacid generator is small, it may take a long time to cure or may not be possible to obtain a sufficiently cured product, whereas if the amount of photoacid generator is large, it may be undesirable because color may remain in the cured product or the coloring or heat resistance or light resistance may be impaired due to rapid curing.

[0073] When the curable resin is a thermosetting resin, it may contain a curing accelerator. Examples of the curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, and imidazole-based curing accelerators. The curing accelerator may be used alone or in combination of two or more.

[0074] Examples of the phosphorus-based hardening accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, etc., and triphenylphosphine and tetrabutylphosphonium decanoate are preferred. As the phosphorus-based hardening accelerator, commercially available products may be used, such as "TBP-DA" manufactured by Hokko Chemical Co., Ltd.

[0075] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5.4.0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5.4.0)-undecene being preferred.

[0076] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 2-methylimidazoline, 2-phenylimidazoline, and the like. As the imidazole-based curing accelerator, a commercially available product may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0077] (Basic compounds) The curable resin may contain a basic compound to improve the remaining film rate and resolution when performing photolithography. The basic compound acts as a quencher. That is, by blending an appropriate amount of the basic compound in the curable resin, it is possible to prevent the crosslinking caused by the photoacid generator from reaching the unexposed portion. This improves the remaining film rate, and the contrast between the exposed portion and the unexposed portion becomes clear, improving the resolution.

[0078] The amount of the basic compound is preferably 0.001 to 2.0 parts by weight, more preferably 0.01 to 1.0 parts by weight, based on 100 parts by weight of the compound having a cationic polymerizable functional group. If the amount of the basic compound is 0.001 parts by weight or more, the effect as a quencher can be sufficiently exhibited. If the amount of the basic compound is 2.0 parts by weight or less, the sensitivity can be improved.

[0079] The weight ratio ((B) / (A)) of the basic compound (B) to the photoacid generator (A) is 0.001 to 0.2, and preferably 0.01 to 0.15. When the weight ratio is 0.001 or more, the basic compound can fully exert its effect as a quencher. When the weight ratio is 0.2 or less, crosslinking can be fully performed.

[0080] The basic compound is not particularly limited, and examples thereof include primary, secondary and tertiary aliphatic amines, mixed amines, aromatic amines, heterocyclic amines, amide derivatives and imide derivatives, etc. Among these, aromatic amines and heterocyclic amines are preferably used as the basic compound.

[0081] Examples of the aromatic amines and the heterocyclic amines include aniline, pyrrole, oxazole, thiazole, imidazole, pyrazole, furazan, pyrroline, pyrrolidine, imidazoline, imidazolidine, pyridine, pyridazine, pyrimidine, pyrazine, pyrazoline, pyrazolidine, piperidine, piperazine, morpholine, indole, isoindole, 1H-indazole, indoline, quinoline, cinnoline, quinazoline, quinoxaline, phthalazine, purine, pteridine, carbazole, phenanthridine, acridine, phenazine, 1,10-phenanthroline, adenine, adenosine, guanine, guanosine, uracil and uridine, and derivatives thereof. Examples of the heterocyclic amines include 2,6-lutidine.

[0082] Among them, morpholine derivatives can be preferably used as the basic compound. Specific examples of the morpholine derivatives include bis(2-morpholinoethyl)ether, 4,4'-carbonyldimorpholine, 4-[2-(ethoxycarbonyl)ethyl]morpholine, and 4-(p-tolyl)morpholine.

[0083] As the heterocyclic amines, hindered amine light stabilizers (HALS) can be used.

[0084] The basic compound may be used alone or in combination of two or more kinds.

[0085] (sensitizer) The curable resin may contain a sensitizer. The sensitizer can improve the sensitivity of the curable resin to visible light and can also impart sensitivity to high wavelength light such as g-line (436 nm), h-line (405 nm) and i-line (365 nm). The curability of the curable resin can be adjusted by using these sensitizers in combination with the photoacid generator. Examples of such sensitizers include anthracene-based compounds and thioxanthone-based compounds.

[0086] Specific examples of the anthracene-based compound include anthracene, 2-ethyl-9,10-dimethoxyanthracene, 9,10-dimethylanthracene, 9,10-dibutoxyanthracene, 9,10-dipropoxyanthracene, 9,10-diethoxyanthracene, 1,4-dimethoxyanthracene, 9-methylanthracene, 2-ethylanthracene, 2-tert-butylanthracene, 2,6-di-tert-butylanthracene, 9,10-diphenyl-2,6-di-tert-butylanthracene, etc. In particular, from the viewpoint of easy availability, anthracene, 9,10-dimethylanthracene, 9,10-dibutoxyanthracene, 9,10-dipropoxyanthracene, 9,10-diethoxyanthracene, etc. are preferred as the anthracene-based compound. As the anthracene-based compound, anthracene is preferred from the viewpoint of excellent transparency of the cured product, and 9,10-dibutoxyanthracene, 9,10-dipropoxyanthracene, 9,10-diethoxyanthracene, and the like are preferred from the viewpoint of excellent compatibility with the photosensitive composition.

[0087] Specific examples of the thioxanthone compounds include thioxanthone, 2-chlorothioxanthone, and 2,5-diethyldioxanthone.

[0088] These sensitizers may be used alone or in combination of two or more.

[0089] The content of the sensitizer is not particularly limited as long as it is an amount that can exert a sensitizing effect, but is preferably 0.01 to 300 mol, more preferably 0.01 to 100 mol, relative to 1 mol of the added photoacid generator. If the amount of the sensitizer is small, the sensitizing effect cannot be obtained, and curing may take a long time or may have an undesirable effect on the developability. On the other hand, if the amount of the sensitizer is large, color may remain in the cured product, coloring may occur due to rapid curing, or heat resistance or light resistance may be impaired.

[0090] (Adhesion improver) The curable resin may contain an adhesion improver. Examples of the adhesion improver include, in addition to commonly used adhesives, various coupling agents, epoxy compounds, oxetane compounds, phenolic resins, coumarone-indene resins, rosin ester resins, terpene-phenolic resins, α-methylstyrene-vinyltoluene copolymers, polyethylmethylstyrene, and aromatic polyisocyanates.

[0091] An example of the coupling agent is a silane coupling agent. The silane coupling agent is not particularly limited as long as it is a compound having at least one functional group reactive with an organic group and at least one hydrolyzable silicon group in the molecule. As the group reactive with an organic group, from the viewpoint of handling, at least one functional group selected from an epoxy group, a methacryl group, an acrylic group, an isocyanate group, an isocyanurate group, a vinyl group, and a carbamate group is preferable, and from the viewpoint of curing property and adhesiveness, an epoxy group, a methacryl group, or an acrylic group is particularly preferable. As the hydrolyzable silicon group, from the viewpoint of handling, an alkoxysilyl group is preferable, and from the viewpoint of reactivity, a methoxysilyl group or an ethoxysilyl group is particularly preferable.

[0092] Examples of preferred silane coupling agents include alkoxysilanes having an epoxy functional group, such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; alkoxysilanes having a methacryl group or an acryl group, such as 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxymethyltriethoxysilane, acryloxymethyltrimethoxysilane, and acryloxymethyltriethoxysilane; tris[3-(trimethoxysilylpropyl)]isocyanurate; and γ-isocyanatepropyltrimethoxysilane. Furthermore, these coupling agents, silane coupling agents, epoxy compounds, etc. may be used alone or in combination of two or more.

[0093] The amount of the silane coupling agent added can be appropriately set, but is preferably 0.1 to 20 parts by weight, more preferably 0.3 to 10 parts by weight, and even more preferably 0.5 to 5 parts by weight, relative to 100 parts by weight of the compound having a cationic polymerizable functional group. If the amount added is small, the adhesiveness improving effect is not achieved, and if the amount added is large, it may have an adverse effect on the curability and physical properties of the cured product.

[0094] (thermoplastic resin) For the purpose of improving the properties of the curable resin, it is also possible to add various thermoplastic resins to the curable resin. Examples of the thermoplastic resin include acrylic resins such as polymethyl methacrylate-based resins (e.g., Optretz manufactured by Hitachi Chemical Co., Ltd.) which are homopolymers of methyl methacrylate or random, block, or graft polymers of methyl methacrylate and other monomers, and polybutyl acrylate-based resins (e.g., homopolymers of butyl acrylate or random, block, or graft polymers of butyl acrylate and other monomers), polycarbonate-based resins such as polycarbonate resins containing bisphenol A, 3,3,5-trimethylcyclohexylidene bisphenol, or the like as monomer structures (e.g., APEC manufactured by Teijin Co., Ltd.), norbornene derivatives, vinyl monomers, or the like homopolymerized or copolymerized resins, norbornene derivatives, or hydrogenated cycloolefin resins (e.g., cycloolefin resins such as hydrogenated norbornene derivatives, vinyl monomers, or the like homopolymerized or copolymerized resins, norbornene derivatives, or hydrogenated norbornene derivatives, etc. For example, APEL manufactured by Mitsui Chemicals, ZEONOR and ZEONEX manufactured by Nippon Zeon Co., Ltd., ARTON manufactured by JSR Corporation, etc.), olefin-maleimide resins such as copolymers of ethylene and maleimide (for example, TI-PAS manufactured by Tosoh Corporation, etc.), polyester resins such as polyesters obtained by polycondensation of bisphenols (bisphenol A and bis(4-(2-hydroxyethoxy)phenyl)fluorene, etc.) or diols (diethylene glycol, etc.) with phthalic acids (terephthalic acid, isophthalic acid, etc.) or aliphatic dicarboxylic acids (for example, O-PET manufactured by Kanebo Co., Ltd., etc.), polyethersulfone resins, polyarylate resins, polyvinyl acetal resins, polyethylene resins, polypropylene resins, polystyrene resins, polyamide resins, silicone resins, fluororesins, etc., as well as rubber-like resins such as natural rubber and EPDM, are listed, but are not limited thereto. As the thermoplastic resin, a single one may be used, or a plurality of thermoplastic resins may be used in combination.

[0095] The thermoplastic resin may have a crosslinkable group. Examples of the crosslinkable group include an epoxy group, an amino group, a radically polymerizable unsaturated group, a carboxyl group, an isocyanate group, a hydroxyl group, and an alkoxysilyl group. From the viewpoint that the heat resistance of the obtained cured product is likely to be high, the thermoplastic resin preferably has one or more crosslinkable groups on average per molecule.

[0096] The molecular weight of the thermoplastic resin is not particularly limited, but from the viewpoint of easily improving compatibility with polysiloxane-based compounds, the number average molecular weight is preferably 10,000 or less, more preferably 5,000 or less. On the other hand, from the viewpoint of easily improving toughness of the obtained cured product, the number average molecular weight is preferably 10,000 or more, more preferably 100,000 or more. There is also no particular limitation on the molecular weight distribution, but from the viewpoint of easily improving moldability by reducing the viscosity of the mixture, the molecular weight distribution is preferably 3 or less, more preferably 2 or less, and even more preferably 1.5 or less.

[0097] The amount of the thermoplastic resin is not particularly limited, but is preferably 5 to 50% by weight, more preferably 10 to 30% by weight, based on the total amount of the curable resin. If the amount of the thermoplastic resin is small, the cured product may become brittle. If the amount of the thermoplastic resin is large, the heat resistance (elastic modulus at high temperatures) is likely to be low.

[0098] The thermoplastic resin may be dissolved in the curable resin and mixed in a uniform state, or may be pulverized and mixed in a particulate state, or may be dissolved in a solvent and mixed to form a dispersed state. In terms of the fact that the obtained cured product is more likely to be transparent, it is preferable to dissolve the thermoplastic resin in the curable resin and mix it in a uniform state. In this case, too, the thermoplastic resin may be directly dissolved in the curable resin, or may be mixed uniformly using a solvent or the like, or the solvent may be removed thereafter to form a uniform dispersed or mixed state.

[0099] When the thermoplastic resin is dispersed, the average particle size of the thermoplastic resin may be appropriately set, but the lower limit of the average particle size is preferably 10 nm, and the upper limit of the average particle size is preferably 10 μm. The particle system may have a distribution, and may be a single dispersion or may have multiple peak particle sizes, but from the viewpoint of low viscosity of the curable composition and good moldability, the coefficient of variation of the particle size is preferably 10% or less.

[0100] (filling material) The above-mentioned curable resin may contain a filler as required.Various fillers are used as the filler, and examples of such fillers include inorganic fillers such as silica-based fillers (quartz, fume silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, and ultrafine amorphous silica), silicon nitride, silver powder, alumina, aluminum hydroxide, titanium oxide, glass fiber, carbon fiber, mica, carbon black, graphite, diatomaceous earth, clay, clay, talc, calcium carbonate, magnesium carbonate, barium sulfate, and inorganic balloon, as well as fillers that are generally used or proposed as fillers for conventional sealing materials, such as epoxy-based fillers.

[0101] (Anti-aging agent) An antioxidant may be added to the curable resin. Examples of the antioxidant include commonly used antioxidants such as hindered phenol-based antioxidants, as well as citric acid, phosphoric acid, and sulfur-based antioxidants.

[0102] As the hindered phenol-based antioxidant, various types can be used, including Irganox 1010 available from BASF.

[0103] Examples of the sulfur-based antiaging agent include mercaptans, mercaptan salts, sulfides (sulfide carboxylates, hindered phenol-based sulfides, and the like), polysulfides, dithiocarboxylates, thioureas, thiophosphates, sulfonium compounds, thioaldehydes, thioketones, mercaptals, mercaptols, monothioacids, polythioacids, thioamides, and sulfoxides.

[0104] These antioxidants may be used alone or in combination of two or more.

[0105] (Radical inhibitor) A radical inhibitor may be added to the curable resin. Examples of the radical inhibitor include phenol radical inhibitors such as 2,6-di-t-butyl-3-methylphenol (BHT), 2,2'-methylene-bis(4-methyl-6-t-butylphenol) and tetrakis(methylene-3(3,5-di-t-butyl-4-hydroxyphenyl)propionate)methane, and amine radical inhibitors such as phenyl-β-naphthylamine, α-naphthylamine, N,N'-sec-butyl-p-phenylenediamine, phenothiazine and N,N'-diphenyl-p-phenylenediamine. These radical inhibitors may be used alone or in combination of two or more.

[0106] (solvent) When the curable resin has high viscosity, it can be dissolved in a solvent before use. The solvent is not particularly limited, and specifically includes hydrocarbon solvents such as benzene, toluene, hexane, and heptane; ether solvents such as tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and diethyl ether; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; glycol solvents such as propylene glycol-1-monomethyl ether-2-acetate (PGMEA) and ethylene glycol diethyl ether; ester solvents such as isobutyl isobutyrate, butyl acetate, and ethyl lactate; halogen-based solvents such as chloroform, methylene chloride, and 1,2-dichloroethane. One of these solvents may be used, or two or more of them may be used as a mixed solvent.

[0107] The amount of the solvent used can be appropriately set, but the preferred lower limit of the amount used per 1 g of the curable resin used is 0.1 mL, and the preferred upper limit of the amount used is 10 mL. If the amount of the solvent used is small, it may be difficult to obtain the effect of using the solvent, such as low viscosity. In addition, if the amount of the solvent used is large, the solvent may remain in the material, which may easily cause problems such as thermal cracking, and may be disadvantageous in terms of cost, resulting in a decrease in industrial value.

[0108] (others) To the curable resin, colorants, release agents, flame retardants, flame retardant assistants, surfactants, defoamers, emulsifiers, leveling agents, anti-repellents, ion trapping agents (antimony-bismuth, etc.), thixotropy imparting agents, tackifiers, storage stability improvers, ozone degradation inhibitors, light stabilizers, thickeners, plasticizers, reactive diluents, antioxidants, heat stabilizers, conductivity imparting agents, antistatic agents, radiation shielding agents, nucleating agents, phosphorus-based peroxide decomposers, lubricants, pigments, metal deactivators, thermal conductivity imparting agents, physical property adjusters, and the like can be added within a range that does not impair the objects and effects of the present invention.

[0109] (Method of manufacturing substrate laminate) Regarding the manufacturing method of the substrate laminate according to the present embodiment, a curable resin containing an organic acidic compound is used as an adhesive layer, and a layer containing the organic acidic compound is formed by generating and adhering the organic acidic compound as an outgas during manufacturing. The manufacturing method of the substrate laminate used in the image sensor will be described in detail with reference to the drawings.

[0110] This method includes the steps of forming an adhesive layer containing a curable resin and at least one organic acidic compound in a pattern on a first substrate, laminating the surface of the first substrate on which the adhesive layer is formed and a second substrate to obtain a laminate, and heating the laminate at 180° C. to 350° C. Either the first substrate or the second substrate is glass containing an alkali component.

[0111] First, a curable resin composition containing a curable resin and at least one organic acidic compound is formed in a pattern on a glass substrate (first substrate) containing an alkaline component as an adhesive layer. In the curable resin composition for forming an adhesive layer, the content of the organic acidic compound is preferably 0.1 to 15 parts by weight, more preferably 0.3 to 10 parts by weight, and even more preferably 0.5 to 5 parts by weight, relative to 100 parts by weight of the curable resin. By setting the content within this range, a layer containing a sufficient amount of the organic acidic compound as outgassing when the adhesive layer is heated and cured is formed. If the amount of the organic acidic compound is less than 0.1 parts by weight, it may be difficult to suppress glass tarnish, and if the amount exceeds 15 parts by weight, the outgassing of the organic acidic compound itself may increase, or impurities may be generated by decomposition of the curable resin forming the adhesive layer, which may cause damage to the substrate, such as a decrease in transparency.

[0112] As a method for forming a pattern of the adhesive layer, when the curable resin is a thermosetting resin, a dispensing method, a pin transfer method, a screen printing method, etc. can be used, and when the curable resin is a photosensitive resin, photolithography can also be used in addition to these.

[0113] In the pattern formation process, when a pattern is formed by photolithography using a negative photosensitive resin, a coating film 11 is first formed on a glass substrate 2 having an alkaline component, which is a first substrate, using a spin coating method, a roll coating method, a bar coating method, or the like (FIG. 1(a)), and then the coating film 11 is irradiated with light through a photomask to harden the exposed portion and form an adhesive layer 1 (FIG. 1(b)). The wavelength of the irradiated light is usually in the range of 200 to 450 nm. Examples of light sources include high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, high-power metal halide lamps, xenon lamps, carbon arc lamps, and light-emitting diodes.

[0114] The exposure dose in the area irradiated with light is preferably 1 to 10,000 mJ / cm 2 , more preferably 1 to 4000 mJ / cm 2 The exposure dose is 1 mJ / cm 2 By setting the exposure dose to 10,000 mJ / cm or more, curing can be promoted. 2 By keeping the time within the range of 1 to 600 seconds, discoloration due to rapid curing can be suppressed. The time for which the coating film is irradiated with light is preferably 1 to 600 seconds, and more preferably 1 to 150 seconds.

[0115] After the exposure, the non-exposed portion is removed from the glass substrate 2 with a developer having an alkaline component, to obtain a patterned adhesive layer 1 (FIG. 1(c)). The developer used here can be appropriately selected depending on the photosensitive resin used, and for example, in the case of solvent development, examples of the developer include the above-mentioned hydrocarbon solvents, ether solvents, ketone solvents, glycol solvents, ester solvents, halogen solvents, etc., and examples of alkaline developer containing an alkaline component include tetramethylammonium hydroxide (TMAH), choline, potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, lithium carbonate, etc.

[0116] The concentration of the alkaline component in the alkaline developing solution is preferably 25% by weight or less, more preferably 10% by weight or less, and even more preferably 5% by weight or less, from the viewpoint of facilitating contrast between the exposed and non-exposed areas. Methods for contacting the non-exposed areas with the alkaline developing solution include immersion, paddle, and spray methods. After development, the film may be washed and dried.

[0117] Next, the glass substrate 2 containing an alkali component having the patterned adhesive layer 1 is laminated so that the adhesive layer 1 side of the glass substrate 2 and the light receiving element 4 side of the semiconductor element substrate 3 (second substrate) face each other to obtain a laminate (FIG. 1(d)), and then the laminate is heated to obtain a substrate laminate. The heating temperature is usually 180°C to 350°C, but is preferably 180°C to 300°C. In addition, in order to adhere the adhesive layer 1 to the semiconductor element substrate 3, which is the second substrate, it is also possible to heat the substrate while applying a load during lamination. The load at this time can be about 10g to 5000g.

[0118] Through the heating process, the organic acidic compound contained in the adhesive layer 1 volatilizes as outgassing and fills the hollow space, resulting in a substrate laminate in which a layer 5 containing an organic acidic compound is formed on the hollow space side of the glass containing alkaline components (Figure 1(e)).

[0119] In the above, the glass substrate 2 containing an alkaline component is used as the first substrate, and the semiconductor element substrate 3 is used as the second substrate, but the present invention is not limited to this. For example, the semiconductor element substrate 3 is used as the first substrate, and an adhesive layer 1 is patterned and formed on the surface of the semiconductor element substrate 3 facing the light receiving element 4 so as to surround the light receiving element 4 (FIG. 2(a)). A glass substrate 2 containing an alkaline component is laminated as the second substrate (FIG. 2(b)). The organic acidic compound is volatilized as outgas by heating, and a layer 5 containing an organic acidic compound is formed on the hollow portion side of the glass substrate 2 containing an alkaline component (FIG. 2(c)).

[0120] In the substrate laminate of this embodiment, when the first substrate and the second substrate are laminated and hardened via the adhesive layer, the organic acidic compound is released as outgassing into the hollow portion and a layer containing the organic acidic compound is formed on the glass substrate containing an alkaline component, which is the first substrate or the second substrate. Therefore, during a high temperature and high humidity test, the organic acidic compound dissolves in the moisture adhering to the glass containing an alkaline component, and the elution of the alkaline component from the glass containing an alkaline component, which is the cause of glass tarnish, can be suppressed. That is, according to this embodiment, a substrate laminate in which glass tarnishing during a high-temperature, high-humidity test is suppressed can be obtained.

[0121] In another method for manufacturing the substrate laminate according to this embodiment, a liquid organic acidic compound is applied in advance to a glass substrate 2 containing an alkaline component so as to cover at least the surface portion of the substrate laminate that will become the hollow portion, or a solution containing an organic acidic compound is applied and dried to form a layer 5 containing an organic acidic compound (FIG. 3(a)). At this time, the solution may be applied only to the surface portion that will become the hollow portion, or may be applied to the entire surface of the hollow portion. Methods for applying the solution containing an organic acidic compound to glass containing an alkaline component include spin coating, roll coating, bar coating, and the like.

[0122] Thereafter, the adhesive layer 1 can be laminated with a semiconductor element substrate 3 (second substrate) having a pattern formed thereon (FIG. 3(b)) to obtain a substrate laminate. The substrate on which the adhesive layer is formed in a pattern can be appropriately selected depending on the type of curable resin and the pattern forming method used. In addition, when using a method in which a layer containing an organic acidic compound is formed in advance, the adhesive layer is formed using a curable resin composition that does not contain an organic acidic compound.

[0123] In this method, since the curable resin composition does not contain an organic acidic compound, the present invention can be applied to curable resin compositions whose pot life is easily affected by organic acidic compounds. EXAMPLES

[0124] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples.

[0125] (Patterning evaluation) The following patterning evaluation samples were prepared for the photosensitive resin compositions (Examples 1 to 7, and Comparative Example 1). First, the photosensitive resin composition was spin-coated on a glass substrate. The obtained substrate was heated on a hot plate heated to 120°C for 10 minutes. Furthermore, using an exposure device (high pressure mercury lamp, manual exposure machine, manufactured by Dai Nippon Kaken Co., Ltd.), exposure was performed with an optimal integrated light amount for each resin composition through a mask engraved with a 1 cm x 1 cm square with a line width of 300 μm (soft contact exposure), and the substrate was left for 5 minutes after exposure. Thereafter, the substrate was immersed in an alkaline developer (a 2.38% aqueous solution of tetramethylammonium hydroxide (TMAH)) for 45 seconds, washed with water for 30 seconds, and the moisture on the surface was removed with compressed air or compressed nitrogen to form a pattern. The obtained patterning evaluation sample was measured for the line width of the formed pattern using a 3D measuring laser microscope (LEXT OLS4000, manufactured by Olympus Corporation), and evaluated according to the following criteria. <Evaluation criteria> ◎: Very good level (line width 200μm±10μm) 〇: Practical level (line width 200μm±20μm) ×: Not suitable for practical use (line width 200μm±30μm)

[0126] (Adhesion evaluation) For Examples 1 to 7 and Comparative Example 1, a silicon wafer cut into 2 cm square was heated to 150° C. on a hot plate, and the above-mentioned patterning evaluation sample was placed on top of it with the surface on which the photosensitive resin was formed facing the silicon wafer side. A load of 800 g was applied from above to bond the resin layer and the silicon wafer together, producing a three-layer laminate of glass, resin film, and silicon wafer.

[0127] For Examples 8-9 and Comparative Examples 2-3, the thermosetting resin composition was applied to a 9 mm x 9 mm square on a glass cut to 1 cm square using a dispenser so that the line width was 200 μm to 400 μm. A silicon wafer cut to 2 cm square was heated to 150°C on a hot plate, and the glass coated with the thermosetting resin composition was placed on the silicon wafer with the resin surface facing the Si wafer. A three-layer laminate of glass, resin film, and silicon wafer was produced by bonding the resin layer and silicon wafer from above while applying a load of 100 g. The obtained adhesion evaluation sample was observed at the glass-resin boundary in the hollow part using a 3D measuring laser microscope (LEXT OLS4000, manufactured by Olympus Corporation) and evaluated according to the following criteria. <Evaluation criteria> ◎: Very good level (no peeling or bubbles in the adhesive area) 〇: Practical level (peeling or bubbles of 100μm or less in the adhesive area) ×: Not suitable for practical use (peeling or bubbles over 100 μm in size in the adhesive area)

[0128] (High temperature and humidity test) The adhesion evaluation sample obtained above was pretreated according to the reliability evaluation JESD22 A101 standard, which examines the resistance of devices / packages to long-term temperature, humidity, and electrical stress. The treated evaluation sample was stored in a constant temperature and humidity chamber (manufactured by Nagano Science Co., Ltd.) at 85°C and 85% for 24 hours, and then left at room temperature and humidity for 3 hours after being removed from the device. The glass surface inside the hollow part of this sample was observed using a 3D measuring laser microscope (LEXT OLS4000, manufactured by Olympus Co., Ltd.) and evaluated according to the following criteria. <Evaluation criteria> ◎: Good level (no discoloration on the glass surface inside the hollow area) 〇: Practical level (stains on the glass surface inside the hollow area at intervals of 50μm or more) ×: Not suitable for practical use (stains on the glass surface within the hollow area at intervals of less than 50 μm)

[0129] (Production Example 1) 40g of diallyl isocyanuric acid and 29g of diallyl monomethyl isocyanuric acid were dissolved in 264g of dioxane, and 139μL of a xylene solution of platinum vinyl siloxane complex (platinum vinyl siloxane complex containing 3% by weight of platinum, manufactured by Umicore Precious Metals Japan, Pt-VTSC-3X) was added. The solution thus obtained was dropped over 3 hours into a solution of 85g of 1,3,5,7-tetrahydrogen-1,3,5,7-tetramethylcyclotetrasiloxane dissolved in 171g of toluene, heated to 105℃ in a nitrogen atmosphere containing 3% oxygen.

[0130] 30 minutes after the end of drip 1 It was confirmed by H-NMR that the reaction rate of the alkenyl group was 95% or more. Then, a solution of 60 g of 1-vinyl-3,4-epoxycyclohexane dissolved in 60 g of toluene was added dropwise to the above solution over a period of 1 hour. 30 minutes after the end of the dropwise addition, 1 After confirming that the reaction rate of the alkenyl groups was 95% or more by H-NMR, the reaction was terminated by cooling. The solvents dioxane and toluene were distilled under reduced pressure and then replaced with isobutyl isobutyrate to obtain "Solution A", a colorless and transparent 70% by weight solution of the cationic curable compound.

[0131] (Examples 1 to 7, Comparative Example 1) A photosensitive resin composition was obtained by mixing and stirring solution A and each component in the ratio shown in Table 1. In Table 1, CPI-210S (manufactured by San-Apro Co., Ltd.) is a photoacid generator, Celloxide 2021P (manufactured by Daicel Corporation) is a bifunctional epoxy crosslinking agent, and KBM-9659 (manufactured by Shin-Etsu Chemical Co., Ltd.) is a silane coupling agent, and the units of the amounts mixed in Table 1 are parts.

[0132] (Examples 8 and 9, Comparative Examples 2 and 3) A thermosetting resin composition was obtained by mixing and stirring the components in the ratio shown in Table 1. In Table 1, jER806 (manufactured by Mitsubishi Chemical Corporation) is a bisphenol F type epoxy resin, SG-70L (manufactured by Nagase Chemtec Corporation) is a carboxyl group-containing acrylic acid ester copolymer resin, MEH-7700 (manufactured by Meiwa Kasei Co., Ltd.) is a phenol-based curing agent, Celloxide 2021P (manufactured by Daicel Corporation) is a bifunctional epoxy crosslinking agent, and KBM-9659 (manufactured by Shin-Etsu Chemical Co., Ltd.) is a silane-based coupling agent, and the units of the amounts mixed in Table 1 are parts.

[0133] [Table 1]

[0134] (result) The above-mentioned evaluations were carried out on the resin compositions obtained in Examples 1 to 9 and Comparative Examples 1 to 3. The results are shown in Table 2.

[0135] [Table 2]

[0136] In Examples 1 to 9, the resin composition contains an organic acidic compound, and the organic acidic compound added in the process of preparing the substrate laminate is sufficiently filled in the hollow portion as outgas, and a layer containing the organic acidic compound is formed on the hollow portion side of the glass containing an alkaline component, which is effective in suppressing the occurrence of tarnish. In particular, Examples 1 to 3, 8, and 9 have an excellent balance of the molecular weight, boiling point, and acidity of the organic acidic compound added, so a high suppression effect against the occurrence of tarnish in the high temperature and high humidity test was obtained. On the other hand, Comparative Examples 1 to 3 do not contain an organic acidic compound in the resin composition, so tarnish occurred in all of them.

[0137] 1: Adhesive layer 2: Substrate containing alkaline components 3: Semiconductor element substrate 4: Light receiving element 5: Layer containing organic acidic compounds 11: Paint film

Claims

1. A substrate laminate having a first substrate, an adhesive layer, and a second substrate, A hollow portion is provided between the first substrate and the second substrate, The adhesive layer is provided on an outer periphery of the hollow portion, Either the first substrate or the second substrate is a glass containing an alkali component, a layer containing an organic acidic compound is provided on a surface of the glass containing an alkali component facing the hollow portion, The substrate laminate, wherein the adhesive layer is a cured product of a curable resin containing 0.1 to 15 parts by weight of an organic acidic compound relative to 100 parts by weight of the curable resin (provided that the organic acidic compound does not include a photoacid generator).

2. The substrate laminate according to claim 1 , wherein the organic acid compound has a boiling point of 300° C. or lower.

3. 3. The substrate laminate according to claim 1, wherein the organic acidic compound has a molecular weight of 300 or less.

4. 4. The substrate laminate according to claim 1, wherein the organic acidic compound has an acid dissociation constant (pKa) of 2.5 to 10.

5. The substrate laminate according to any one of claims 1 to 4, wherein the organic acidic compound has at least one functional group selected from the group consisting of a carboxyl group, a phosphorus (P)-containing acidic group, a phosphorus (P)-containing ester group, a sulfo group, a sulfonyl group, an amide group, and a cyanuric group.

6. The substrate laminate according to any one of claims 1 to 5, wherein the adhesive layer comprises at least one resin selected from the group consisting of an epoxy resin, an acrylic resin, a polyimide resin, a phenolic resin, and a silicone resin.

7. The substrate laminate according to any one of claims 1 to 6, wherein the adhesive layer has cationic polymerization properties.

8. The substrate laminate according to any one of claims 1 to 7, wherein the adhesive layer is a photosensitive resin.

9. The substrate laminate according to any one of claims 1 to 8, wherein the adhesive layer is alkali-soluble.

10. The substrate laminate according to any one of claims 1 to 9, wherein the other of the first substrate and the second substrate is a semiconductor device substrate.

11. forming an adhesive layer containing a curable resin and at least one organic acidic compound on a first substrate in a pattern; laminating a surface of the first substrate on the side of the adhesive layer and a second substrate to obtain a laminate; Heating the laminate at 180°C to 350°C; Either the first substrate or the second substrate is a glass containing an alkali component, a hollow portion surrounded by the first substrate, the second substrate, and the adhesive layer; The method for producing a substrate laminate, wherein the adhesive layer is a curable resin containing 0.1 to 15 parts by weight of an organic acidic compound relative to 100 parts by weight of the curable resin (provided that the organic acidic compound does not include a photoacid generator).

12. The method for manufacturing a substrate stack according to claim 11 , wherein the other of the first substrate and the second substrate is a semiconductor device substrate.

Citation Information

Patent Citations

  • JP1974076916A

  • Compositions for coating glass sheets

    JP2001522740A

  • Photosensitive adhesive composition and laminate using the composition, or solid-state imaging device and method of manufacturing the imaging device

    JP2012041410A

  • Substrate laminate, and image sensor using the laminate

    JP2019081342A

  • Back sealing member for organic electroluminescence device, glass substrate for organic electroluminescence device, organic electroluminescence device, and methods for manufacturing sealing member and glass substrate

    WO2003065769A1